Praktik Kerjasama Bagi Hasil Pada Usaha Pangulong Kayu Miharja Jati Dalam Perspektif Akad Mudharabah - Sofie Mutiara Rahmadona; Relit Nur Edi; Muslim (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the profit-sharing partnership practiced at Panglong Kayu Miharja Jati, Way Halim District, Bandar Lampung, and assess its conformity with the principles of the mudharabah contract under Islamic economic law. This qualitative study employed a field research design with a descriptive-analytical approach. Primary data were obtained through interviews with the capital owner and business manager, while secondary data were drawn from relevant Islamic economic law literature. The findings show that the partnership substantially reflects the characteristics of a mudharabah contract. The capital owner provides the business capital, while the manager conducts the operational activities, with net profits divided at a 60:40 ratio. Losses are differentiated according to their causes: losses resulting from external factors, such as declining orders and increasing raw material prices, are borne by the capital owner, whereas losses caused by the manager’s technical negligence are borne by the manager. However, the practice does not fully comply with the ideal principles of mudharabah because the profit-sharing ratio is based only on an oral agreement, contract documentation is limited, and financial records lack transparency. These findings indicate substantive conformity alongside administrative weaknesses in the implementation of the contract. Therefore, a written agreement, systematic financial recording, and clear risk allocation are necessary to strengthen fairness, legal certainty, and transparency in the partnership.